Analisis Faktor yang Mempengaruhi Optimalisasi Pengelolaan Aset Barang Milik Daerah (Studi Pada RSUD Mardi Waluyo Kota Blitar) - Kumalasari, Indah; Sitinjak, Norman Duma; Parawiyati, Parawiyati (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to analyze the factors that affect the optimization of the management of Regional Property (BMD) assets at Mardi Waluyo Hospital, Blitar City. The main focus of the study covers five main aspects: planning, procurement, use, utilization, and securing and maintaining assets. The sample in this study is 53 employees. The data analysis technique uses multiple regression analysis. The results of the study showed that planning and procurement had a positive effect on optimizing BMD asset management, which indicated that the better the planning and procurement process, the more optimal the management of these assets. On the other hand, the use and utilization aspects do not have a positive influence, which is caused by a lack of understanding regarding the importance of asset ownership status and the physical condition of damaged assets. Meanwhile, the security and maintenance aspects show a positive impact, indicating that asset management will be more optimal if security and maintenance are carried out properly and sustainably. These findings provide important implications for regional asset management, particularly in improving the efficiency and effectiveness of BMD management in the hospital environment.